Diagnosis of Autoimmune Diseases: Nanocage‐Based Capture‐Detection System for the Clinical Diagnosis of Autoimmune Disease (Small 25/2021). Issue 25 (24th June 2021) - Zhang, Yanan; Li, Yingni; Zhang, Jianlin; Chen, Xuehui; Zhang, Ruofei; Sun, Guoming; Jiang, Bing; Fan, Kelong; Li, Zhanguo; Yan, Xiyun
Abstract : In article number 2101655, Kelong Fan, Zhanguo Li, Xiyun Yan, and co‐workers develop a highly sensitive platform for diagnosis of autoimmune disease. The antigen and anti‐Fc peptides are displayed on the surface of ferritin to construct nanocage‐based capture‐detection system. Multimeric display significantly enhances their binding ability to corresponding antibodies, thus improving the detection sensitivity 100–1000‐folds higher than that of conventional ELISA methods.